2018
DOI: 10.3389/fneur.2018.00620
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa-Carbidopa Intestinal Gel in Parkinson's Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Levodopa has been widely used and regarded as the most effective therapy for Parkinson's disease (PD), but long-term treatment with oral levodopa may result in motor fluctuations and involuntary movements (dyskinesias). There is evidence to suggest that Continuous infusion of levodopa-carbidopa intestinal gel (LCIG) can effectively manage motor and non-motor complications in PD, but clinical studies investigating this have yielded inconsistent results. This systematic review and meta-analysis was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 47 publications
1
41
0
2
Order By: Relevance
“…Nonetheless, currently there are few articles available that analyze the reasons that led to the discontinuation of treatment on large groups of patients. [7][8][9][10] The LCIG therapy became available in Romania in 2009. In 2016 a multicenter study was published analyzing data of the first 113 Romanian patients (9 university teaching hospital centers).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, currently there are few articles available that analyze the reasons that led to the discontinuation of treatment on large groups of patients. [7][8][9][10] The LCIG therapy became available in Romania in 2009. In 2016 a multicenter study was published analyzing data of the first 113 Romanian patients (9 university teaching hospital centers).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the replacement of lost dopamine with dopaminergic drugs in 24 h is necessary for the management of motor symptoms alone – regardless of whether these occur nocturnally or during the daytime. Adjunctive medications [ 31 33 ], infusion systems such as DuoDopa (carbidopa/levodopa) [ 34 ], continuous dopamine delivery treatments like the transdermal rotigotine patch [ 35 39 ], and oral extended release versions of dopamine agents [ 40 , 41 ] have shown significant promise in ameliorating wearing-off effects and symptom fluctuations, in nocturnal as well as daytime symptoms. In a randomized, placebo-controlled study (the RECOVER trial, quality score, 93%), patients with unsatisfactory control of early morning motor symptoms were evaluated on the PDSS-2 and UPDRS III.…”
Section: Discussionmentioning
confidence: 99%
“…LCIG is a well-established and approved therapy designed for continuous infusion into the proximal jejunum via percutaneous endoscopic gastrojejunostomy tube connected to a portable infusion pump [111,112]. Because of its invasive delivery system and associated risks (eg, pain, tube detachment, weight loss), LCIG is indicated for patients with motor fluctuations who have not benefited from other adjunctive treatments [111].…”
Section: Intrajejunalmentioning
confidence: 99%
“…Because of its invasive delivery system and associated risks (eg, pain, tube detachment, weight loss), LCIG is indicated for patients with motor fluctuations who have not benefited from other adjunctive treatments [111]. A systematic review of eight controlled clinical trials showed that LCIG treatment in patients with PD significantly reduced OFF time and related dyskinesias, although it posed a risk of surgical and device-related adverse events [112].…”
Section: Intrajejunalmentioning
confidence: 99%